1992
DOI: 10.1152/jappl.1992.72.3.836
|View full text |Cite
|
Sign up to set email alerts
|

Effect of competition on performance of thoroughbred racehorses

Abstract: The effect of competition and the influence of age and sex on performance were examined in a study of 18 Thoroughbred racehorses. The horses performed two solo and two competitive runs at 1,200 and 1,600 m for a total of eight runs. No group ran faster during competition, which may have been a reflection of the quality of horses used for this study and their susceptibility to stress-induced impairment of performance. Males showed no significant difference between competitive and solo run times, whereas females… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

1993
1993
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 6 publications
0
13
0
Order By: Relevance
“…The effect of competition was small, but indicated that the presence of one or more horses within a horse length distance increases speed. Harkins et al (1992) showed that speed of all investigated Thoroughbred horses was lower during competitive races (another horse participated) than during individual races, which was explained by an earlier onset of fatigue and higher plasma lactate values during competitive races. The investigated horses were not quality racehorses, because they were donated for equine research due to poor racing performance, and could therefore be considered as low-ability horses (Harkins et al, 1992).…”
Section: )mentioning
confidence: 84%
See 2 more Smart Citations
“…The effect of competition was small, but indicated that the presence of one or more horses within a horse length distance increases speed. Harkins et al (1992) showed that speed of all investigated Thoroughbred horses was lower during competitive races (another horse participated) than during individual races, which was explained by an earlier onset of fatigue and higher plasma lactate values during competitive races. The investigated horses were not quality racehorses, because they were donated for equine research due to poor racing performance, and could therefore be considered as low-ability horses (Harkins et al, 1992).…”
Section: )mentioning
confidence: 84%
“…Heritability estimates of speed vary from low to moderate (Villela et al, 2002;Ekiz et al, 2005b). Sex and age of a horse, trainer, track condition, racing distance, number of horses participating in a race, weather condition, carried weight, position in starting gates, and competition have been suggested as possible environmental factors affecting speed (Harkins et al, 1992;Oki et al, 1994;Mota et al, 1998). However, most studies investigated Thoroughbred horses (Oki et al, 1994;Martin et al, 1996;Ekiz et al, 2005b;Mota et al, 2005), whereas few studies identified environmental factors affecting speed of Arabian horses (Ekiz and Koçak, 2005;Ekiz et al, 2005a).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Given that competition has been construed as an acute stress~Harkins, Kamerling, & Church, 1992;Jones & Hardy, 1990;McKay, Selig, Carlson, & Morris, 1997!, it is surprising that we know so little about the cardiovascular impact of competition, particularly interpersonal sports competition. Based on social evaluation theorỹ Festinger, 1954!, Martens~1976!…”
mentioning
confidence: 99%
“…This model described Jaitner and Reinhardt (2003) and Koenen (2002 Influence of gender to the horse performance has been identified in the various disciplines of equestrian sport (Gaffney and Cunningham, 1988;Harkins et al, 1992).…”
Section: Resultsmentioning
confidence: 99%